Fourier transforms and approximations - Sedletskii, A. M. (Analytical methods and special functions, 2000)
Three classes of Fourier transforms are presented: Fourier (Laplace) transforms on the halfline, Fourier transforms of measures with compact support and Fourier transforms of rapidly decreasing functions (on whole line) The focus is on the behaviour of Fourier transforms in the region of analyticity and the distribution of their zeros. Applications of results are presented: approximation by exponentials on the finite interval; behavior of the nonharmonic Fourier series; Muntz-Szasz's problem of approximation by powers on unit interval; approximation by weighted exponentials on whole line.